MATERIALS FOR A REVISION OF LAURACEAE IV* - a. j. g. h. kostermans (REINWARDTIA, 1974)
In the genus Actinodaphtie Nees one new combination and one new species ace presented; in LAndera Thunb. one new combination, 4 new species and one new forma; in lAtsea Lam. one species has been reduced to synonymy, one nomen novum is presented, 5 new species are described and of 6 species new cecords are given; one species has been reinstated. The obscure Mackilus sericea Bl. is a3sumed to be conspecific with Persea bombyeina (King ex Hook, f.) Kosterm. In the genus Persea Mill. one nomen novnm, two new combinations and one new species are created and proposed. In the genus Phoebe Nees one new combination and two new species are presented